ANALISIS KINERJA BADAN USAHA MILIK DESA (BUMDES) DIDESA POHUWATO KABUPATEN POHUWATO (ACCOUNTING STUDY PROGRAM, UNIVERSITAS MUHAMMADIYAH BERAU, 2019)
This study aims to analyze the performance of village-owned enterprises (BUMDes) in terms of service aspects. analyze the Performance of Village-Owned Enterprises (BUMDes) in terms of the Accountability Aspect. analyze the Performance of Village-Owned Enterprises (BUMDes) in terms of aspects of improving living standards. And to analyze the Performance of Village-Owned Enterprises (BUMDes) in terms of compliance with the Law has been implemented. The research method used is a qualitative research method using research informants. The results of the research show that service performance, profitability and sustainability related to operational standards are good, it is necessary to improve the quality and quantity of management and administration training for managers or administrators as well as supervision from parties in the Village Community Empowerment Agency (BPMD), so that it remains created service standards that remain flexible but have authority, strict and selective boundaries and are able to find the best solution in each case. Performance Aspect of Accountability and Village Asset Development The conclusion is that the asset management strategy (increased accountability) undertaken by BUMDES in Pohuwato Village has contributed and can increase village income. Performance Performance Improvement Aspects can be concluded that the presence of BUMDes in the Village of Pohuwato has added income for the management, commissioners and also the people involved, and has been able to reduce the number of unemployed young people in the village, especially fishing communities who live on the coast. In addition, the existence of fishermen depots and fishing stalls in Pohuwato Village can indirectly save fishermen's transportation costs. Compliance with the Laws and Regulations of BUMDes management has been carried out in accordance with financial reporting, service, and SHU distribution has been carried out according to regulations. Penelitian ini bertujuan Untuk menganalisis Kinerja Badan Usaha Milik Desa (BUMDes) ditinjau dari Aspek Pelayanan. menganalisis Kinerja Badan Usaha Milik Desa (BUMDes) ditinjau dari Aspek Akuntabilitas. menganalisis Kinerja Badan Usaha Milik Desa (BUMDes) ditinjau dari Aspek Peningkatan Taraf Hidup. Dan Untuk menganalisis Kinerja Badan Usaha Milik Desa (BUMDes) ditinjau dari Aspek Ketaatan terhadap Undang-undang telah dilaksanakkan. Metode penelitian yang digunakan adalah metode penelitian kualitatif dengan menggunakan informan penelitian. Hasil penelitian menunjukkan pada Kinerja Pelayanan, Keuntungan dan Keberlanjutan terkait standar operasional sudah baik, maka perlu ditingkatkan kualitas dan kuantitas pelatihan-pelatihan manajemen dan administrasi untuk para pengelola atau pengurus juga dilakukan pengawasan dari pihak di Badan Pemberdayaan Masyarakat Desa (BPMD), agar tetap tercipta standar pelayanan yang tetap fleksibel namun memiliki wibawa, batasan-batasan tegas dan selektif serta mampu mencari solusi terbaik dari setiap kasus. Kinerja Aspek Akuntabilitas dan Perkembangan Aset Desa diperoleh kesimpulan bahwa Strategi manajemen aset (peningkatan akuntabilitas) yang telah dilakukan oleh BUMDES di Desa Pohuwato ini telah berkontribusi sekaligus dapat meningkatkan pendapatan desa. Kinerja Aspek Peningkatan Taraf Hidup dapat disimpulkan bahwa dengan hadirnya BUMDes di Desa Pohuwato telah menambah penghasilan bagi pengurus, komisaris dan juga masyarakat yang terlibat, serta telah mampu mengurangi jumlah pengangguran anak muda yang ada di desa terutama masyarakat nelayan yang tinggal di pinggiran pantai. Selain itu juga dengan adanya depot nelayan dan kios nelayan di Desa Pohuwato secara tidak langsung dapat menghemat biaya transportasi nelayan. Ketaatan terhadap Peraturan Perundang-Undangan pengelolaan BUMDes telah dilakukan sesuai dengan pelaporan keuangan, pelayanan, dan pembagian SHU telah dilaksanakan sesuai peraturan.